Analysis of Consumer Attitudes and Performance Attributes of Various Processed Milkfish in Glagah District, Lamongan Regency, East Java - Ika Purnamasari; Moch Saad (Faculty of Fisheries and Marine Science, Brawijaya University, 2021)
Consumers are holders of important information in the management and planning of business development. The purpose of the study is to analyze consumer attitudes towards various processed milkfish and analyze the performance of product attributes of various processed milkfish in Glagah District, Lamongan Regency. The data analysis method used is descriptive analysis, Fishbein attitude model and Importance Performance Analysis (IPA). The results showed that the respondent's assessment of the processed otak-otak and smoked milkfish stated a neutral attitude, and the respondent's assessment of the shredded milkfish and crackers stated a positive attitude. The performance attributes of various processed milkfish included in quadrant I measure the processed otak-otak and the processed abon. Attributes included in quadrant II are taste and price for processed otak-otak, smoked, and crackers, while shredded milkfish only have tasted attributes. Attributes included in quadrant III are product packaging and ease of access for all kinds of milkfish preparations. Attributes included in quadrant IV are the size of the product for shredded and milkfish crackers. It does recommend that producers of otak-otak and smoked milkfish improve their products to get a positive attitude from customers.